Doppëlgangers, degenerations and revolutionary feedbacks in Angola - Blanes, R. L. (Revista de Antropologia, 2025)
In this article I describe the emergence of the so-called Revolutionary Movement ("Revú") in Angola, which appeared in 2011 in the aftermath of the Arab Spring. Based on my ethnographic fieldwork with this movement since 2015, I will debate how this revolutionary emergence is an epistemological feedback against a previous revolutionary process in the country – that of the liberationist and independence movements in the 1960s and 1970s. Invoking concepts of cyclicity (Gonçalves 2017; Blanes 2019) and rhetorical feedback, I will describe an effect of ‘mutual epistemology’ between both revolutionary processes, through which the perception of one is dynamically determined by the perception of the other. In this framework, more than a mimetic revolutionary semiotic, I will entertain the idea of a ‘revolutionary doppëlgangers’, the concurrent construction of ‘evil twins’ as part of a process of political dialectic between regime enablers and oppositionists.